Purification of Citrus Tristeza Virus and Generation of Monospecific Polyclonal Antiserum - Moh. Usman, Nurhadi (2002)
Symptomatology, molecular weight of coat protein (CP) determination and purification procedure for citrus tristeza virus (CTV) antigen were studied to generate monospecific polyclonal antiserum. Results of survey indicated that CTV was found to attack citrus varieties such as C. grandis, C. aurantifolia, C. reticulata, C. hystrix, C. nobilis and C. sinensis with variable symptoms and degrees of severity. Virus complex varied among citrus varieties and cultivars, and there were four important sub isolates found, namely mandarin stem pitting, orange stem pitting, pomelo small fruit, and pomelo mild isolate. In partial purification step, antigen was concentrated by polyethylene glycol (PEG) precipitation followed by low speed centrifugation. Semi purified antigen was then finally purified by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SOS-PAGE). A major protei n band containing CP was excised and eluted using elution buffer containing 0.25 M Tris-HCI pH 6.8+0.1% SOS. With a starting material consisting of 50-gram bark tissue of semi dormant flush, 750 ug of eluted CP as monospecific antigen was obtained. The use of PEG and NaCI for virus precipitation combined with low speed centrifugation in semi purification step, then followed by electrophoresed of semi purified virus preparation in final purification step effectively minimized virus losses during purification processes and minimized possible contamination of plant components in the final immunogen. Monospecific polyclonal antiserum against citrus tristeza virus was generated using the viral CPo Upon SOS-PAGE of local CTV isolate designated as UPM/T002, two protein bands specific for CTV with molecular weight of 25 kOa and 33 kOa were obtained. The major band with molecular weight of 25 kOa that reacted strongly with commercial polyclonal antibody in double antibody sandwich enzyme-linked immunosorbent assay (OAS-E LlSA), was used as the antigen for injection into female White Leghorn chicken.